Prevalence and factors associated with anxiety and depression among the older people in ethnic minority areas in southern China: a cross-sectional study - Suyi Wu; Liu Yang; Haini Mo; Li Li; Zirong Li; Yanping Ying (Frontiers in Public Health)
BackgroundMental health issues among the older people are increasingly becoming a focus of societal concern, with depression and anxiety being common psychological problems that affect their quality of life and physical health. However, research on anxiety and depression among ethnic minorities in China remains relatively limited. This study investigates ethnic disparities in mental health among older adults (≥65 years) in China’s Guangxi Zhuang Autonomous Region, employing a Social Determinants of Health (SDH) framework.MethodsA cross-sectional study was conducted using a multi-stage stratified sampling method among 1,671 older individuals aged 65 and above in five communities in Guangxi from April to May 2024. A total of 1,550 completed questionnaires were collected. Descriptive analysis, univariate analysis, and two-factor logistic regression analysis were employed to explore the influencing factors of depression and anxiety among the older people in ethnic minority areas.ResultsThe prevalence rates of anxiety and depression were 11.42 and 15.94%, respectively. Logistic regression analysis indicated that being female, belonging to ethnic minorities (such as Jing, Yao, Mulao, and Zhuang), cognitive impairment, holding negative attitudes towards aging, and poor psychological resilience were common and significant predictors of both anxiety and depression. Support from children and access to medical insurance emerged as common protective factors against anxiety and depression.ConclusionThe incidence of anxiety and depression symptoms among the older people in the Guangxi Zhuang Autonomous Region is relatively high. Specifically, ethnic minorities such as Jing, Yao, Mulao, and Zhuang exhibited a higher likelihood of experiencing anxiety and depression compared to non-ethnic minorities like Han. This finding highlights the multiple mental health challenges faced by these groups in terms of socioeconomic status, culture, education, and healthcare access. The government should prioritize the mental health of ethnic minorities by optimizing the allocation of social resources and promoting culturally adapted mental health services to address these challenges.